Pengaruh Kompetensi Karyawan, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Sistem Informasi Akuntansi Di LPD - Valentino Anggara, Wayan Putra; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p29, 2019)
More practical data processing through the application of SIA with application programs, but the level of knowledge of human resources in the field of information technology is still limited. In general, the problems of the LPD in Tegallalang District are caused by a lack of quality human resources. The research objective was to determine the effect of employee competency, work motivation, and job satisfaction on the performance of accounting information systems in the LPD of Tegallalang District. The study population included LPD in Tegallalang District, which numbered 43 LPD. The sampling technique used in this study is a saturated sample technique. The hypothesis was tested using multiple linear regression analysis. The results showed that the influence of employee competency, work motivation, and job satisfaction had a positive and significant effect on the performance of accounting information systems. Keywords: Performance of accounting information systems, employee competencies, work motivation, job satisfaction.